2014
DOI: 10.1002/anie.201402934
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Inverse Electron Demand Hetero‐Diels–Alder Reaction with Allylsilanes

Abstract: The first diastereo- and enantioselective inverse electron demand hetero-Diels-Alder reaction of β,γ-unsaturated α-ketoesters with allylsilanes is described. Chiral copper(II) catalysts successfully activate the β,γ-unsaturated α-ketoesters and promote the reaction with allylsilanes with excellent enantioselectivities. This process represents a new entry to chiral oxanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…Evan and co‐workers have developed enantioselective, chiral oxazoline–copper(II) catalysts for hetero‐iEDDA reactions between acyl phosphonates and enol ethers and for the preparation of dihydropyrans . The Ishihara group has developed a chiral copper catalyst to enable enantioselective hetero‐iEDDA reactions between keto esters and allylsilanes . Feng et al.…”
Section: Mechanistic Studies Of the Iedda Reactionmentioning
confidence: 99%
“…Evan and co‐workers have developed enantioselective, chiral oxazoline–copper(II) catalysts for hetero‐iEDDA reactions between acyl phosphonates and enol ethers and for the preparation of dihydropyrans . The Ishihara group has developed a chiral copper catalyst to enable enantioselective hetero‐iEDDA reactions between keto esters and allylsilanes . Feng et al.…”
Section: Mechanistic Studies Of the Iedda Reactionmentioning
confidence: 99%
“…2a ) 13 . Later, Ishihara and co-workers disclosed that bis(oxazoline)/copper(II) species could promote the enantioselective hetero-Diels–Alder (HDA) reaction of β,γ-unsaturated ketoesters with allyl silanes 14 . In addition, Zhang and co-workers demonstrated that the same β,γ-unsaturated ketoester substrates could react with vinylindoles in the presence of an imidodiphosphoric acid to produce [4 + 2] cycloadducts 15 .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, Snapper′s group first described a Cu(OTf) 2 /box catalyzed 1,4‐conjugate addition of allyltrimethylsilane to activated cyclic enones without control of the diastereoselectivity owing to keto‐enol tautomerism of products (Scheme 1.2 c) [7e] . Moreover, as less nucleophilic alkenes, allylsilanes have been employed in annulations [8] and hetero‐Diels–Alder (HDA) reactions [9] . In this regard, the group of Franz described the only example of asymmetric catalytic allylsilane carboannulation with alkylidene oxindoles by the use of the Sc III /indapybox complex as the catalyst (Scheme 1.2 b) [8b] .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the group of Franz described the only example of asymmetric catalytic allylsilane carboannulation with alkylidene oxindoles by the use of the Sc III /indapybox complex as the catalyst (Scheme 1.2 b) [8b] . In 2014, Ishihara, Sakakura, and co‐workers established the unique catalytic enantioselective HDA reaction of allylsilanes to β,γ‐unsaturated α‐ketoesters (Scheme 1.2 d) [9] . Despite these advances, the development of new asymmetric reactions with allylsilanes is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%